Analyses of State and Density of Traffic in the Port of Dubrovnik- Gruz - Jelavić, Vedran; Brajović, Miloš; Đurđević-Tomaš, Ivica (Promet - Traffic&Transportation, 2008)
Port of Gruž is located in a naturally protected bay whichcan accommddate the biggest passenger cmisers and RO-ROships that sail the Mediterranean. At the same time there aremore yachts/'visiting the port because of the vicinity of theDubrovnik historic sites. The frequency of maritime traffic andother mariti~e services is rapidly increasing and sometimescausing owfrload in the summer months. The sizes of all kindsof ships a~d yachts that manoeuvre in the port are getting bigger.The itinerary for the following seasons and prognoses till2010 stress the increase in the number of ships, vehicles andpassengers. The activities at the passenger terminal are in progressat the moment and after completing all the works the passengerpier will be about BOOm long with the depth of 12m.Handling of cmisers will therefore be much easier and more efficient.Another benefit for the bay will be the construction ofthe Yacht marina and marina for the local boats all along thesouth-west coast of the bay. Considering summer peaks in allkinds of traffic it is necessary to analyse the state of all relevanttraffic factors and the density of traffic in order to organise safeand smooth flow of ships, vehicles and passengers through theport of Dubrovnik - Gmi.